Validity and Diagnostic Ability of Pancreatic Exocrine Insufficiency Questionnaire in Turkish Patients - Oğuz, Dilek; Kalkan, İsmail Hakkı; Soytürk, Müjde; Demir, Kadir; Oruç, Nevin; Bengi, Göksel; Gül, Özlem; Ünal, Nalan Gülşen; Örmeci, Aslı Çiftibaşı (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Pancreatic exocrine insufficiency (PEI) is a prevalent disease that is often underdiagnosed and undertreated, leading to resulting in diminished health-related quality of life. The PEI questionnaire (PEI-Q), a patient-reported outcome questionnaire developed to diagnose and evaluate PEI, is available only in English. The study aimed to provide a Turkish translation of PEI-Q and validate its reliability and diagnostic performance in a Turkish-speaking population with PEI. Materials and Methods: This study included 161 participants: 98 patients with PEI and 63 healthy controls. Participants underwent the PEI-Q test, and the results were statistically analyzed for reliability and validity. The diagnostic value of PEI-Q was determined using receiver operating characteristic (ROC) curves. Cronbach’s alpha was used to assess internal consistency, while exploratory factor analysis was performed to determine construct validity and reveal the factor structure. Results: The mean age of participants was 45.0 years, and 60.2% were male. Participants with PEI were significantly older than those without. Scores for abdominal, bowel movement, and total symptoms were significantly higher in patients with PEI than in controls. ROC analysis revealed good diagnostic value for PEI-Q, with areas under the curve ranging from 0.798 to 0.851 for different symptom scores. Cronbach’s alpha coefficients were above 0.70, indicating good internal consistency, and exploratory factor analysis supported a 4-factor structure, accounting for 68.9% of the total variance. Conclusion: The Turkish version of the PEI-Q is a reliable, easy-to-use, and valid screening tool for diagnosing PEI. It consistently assesses symptoms and quality of life in patients with PEI, helping to inform diagnosis and treatment. Cite this article as: Oğuz D, Kalkan İH, Soytürk M, et al. Validity and diagnostic ability of pancreatic exocrine insufficiency questionnaire (PEI-Q) in Turkish patients. Turk J Gastroenterol. 2024;35(9):735-742.